Molecular Detection of Leishmania Infection in Phlebotomine Sand Flies from an Endemic Focus of Zoonotic Cutaneous Leishmaniasis in Iran - Sadegh Mohammadi-Azni; Mohsen Kalantari; Behrad Pourmohammadi (Tehran University of Medical Sciences, 2023)
Background: Due to the outbreak of zoonotic cutaneous leishmaniasis (ZCL), a disease caused by Leishmania major and mainly transmitted by Phlebotomus papatasi, in Damghan City, Semnan Province, the probable vectors of the disease were investigated in the city from 20 March 2016 to 20 January 2018. Methods: Sand flies were collected from indoors and outdoors biweekly by sticky traps in different parts of the city. The trapped sand flies were stored in 70% ethanol. They were identified and checked for Leishmania infections using nested-PCR method and specific primers; CSB1XR, CSB2XF, LiR, and 13Z.  Results: Overall, 1862 phlebotomine sand flies of Ph. papatasi (48.8%), Ph. andrejevi (8.3%), Ph. caucasicus (7.7), Ph. mongolensis (2%), Ph. sergenti (1.2%), Ph. alexandri (0.7%), Sergentomyia murgabiensis sintoni (29.3%), and Se. sumbarica (2%) were collected indoors (31.1%) and outdoors (68.9%). The highest and lowest numbers of collected sand flies were belonging to Ph. papatasi (48.8%) and Ph. alexandri (0.7%) respectively. 2.2% of the examined sand flies were shown to be infected with L. major and all were belonging to Ph. papatasi. Conclusion: This study confirms the report of Ph. papatasi infection with L. major and also the existence of Ph. sergenti and Ph. alexandri, the potential vectors of L. tropica and L. infantum respectively, in Damghan City. According to the findings, it is necessary for health officials to plan and take action to prevent the occurrence of ZCL epidemic in the city as well as the occurrence of other forms of leishmaniasis.